Predictive and prognostic values of serum C1q/tumor necrosis factor-related protein 9 for first-ever ischemic stroke - Zhang, Yan-Qing; Zhang, Hai-Feng; Liu, Xiao-Gang; Li, Rong (Frontiers in Neurology, 2025)
BackgroundThe C1q/Tumor Necrosis Factor-related Protein 9 (CTRP9) is a relatively novel adipokine having showed protection on cerebrovascular system. However, its clinical values have not been well established. This work is to evaluate CTRP9 as predictors of onset risk and outcome of ischemic stroke.MethodsOne thousand one hundred and twenty-three patients undergoing first-ever ischemic stroke and 835 controls were enrolled. Serum CTRP9 was determined within 24 h after the onset. One thousand and twenty-six patients were successfully followed up for all-cause and cardiovascular deaths. Stepwise regression was conducted to screen the independent factors of stroke onset in the whole sample and mortality in the patient subgroup. Survival curves were plotted to evaluate the effect of baseline serum CTRP9 on 3-year all-cause and cardiovascular mortalities of stroke patients.ResultsAt baseline, prevalence of first-ever onset of ischemic stroke in high CTRP9 group was significantly lower than that in low CTRP9 group (p < 0.05) in non-hyperlipidemic subjects. Accumulative all-cause and cardiovascular mortality of patients with high baseline CTRP9 was significantly lower for the first year post stroke onset (p < 0.05). Baseline low CTRP9 was one of the independent risk factors of 3-year all-cause mortality (p < 0.05) of ischemic stroke patients.ConclusionHigh serum CTRP9 exerted protection against first-ever onset of ischemic stroke in non-hyperlipidemic subjects, and also protected general stroke patients against all-cause and cardiovascular mortality at least 1 year post stroke onset. Our findings in this study may pinpoint both the predictive and prognostic values of CTRP9 as a promising biomarker.